Oligomerization Propensity and Flexibility of Yeast Frataxin Studied by X-ray Crystallography and Small-Angle X-ray Scattering. - Söderberg, Christopher; Shkumatov, Alexander V; Rajan, Sreekanth; Gakh, Oleksandr; Svergun, Dmitri I; Isaya, Grazia; Al-Karadaghi, Salam (Journal of Molecular Biology, 2011)
Frataxin is a mitochondrial protein with a central role in iron homeostasis. Defects in frataxin function lead to Friedreich's ataxia, a progressive neurodegenerative disease with childhood onset. The function of frataxin has been shown to be closely associated with its ability to form oligomeric species; however, the factors controlling oligomerization and the types of oligomers present in solution are a matter of debate. Using small-angle X-ray scattering, we found that Co(2+), glycerol, and a single amino acid substitution at the N-terminus, Y73A, facilitate oligomerization of yeast frataxin, resulting in a dynamic equilibrium between monomers, dimers, trimers, hexamers, and higher-order oligomers. Using X-ray crystallography, we found that Co(2+) binds inside the channel at the 3-fold axis of the trimer, which suggests that the metal has an oligomer-stabilizing role. The results reveal the types of oligomers present in solution and support our earlier suggestions that the trimer is the main building block of yeast frataxin oligomers. They also indicate that different mechanisms may control oligomer stability and oligomerization in vivo.